2023
DOI: 10.1039/d3gc01952g
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymeric hydrogel electrolytes obtained by using natural polysaccharide–poly(itaconic acid-co-2-hydroxyethyl methacrylate) in deep eutectic solvents for rechargeable Zn–air batteries

M. E. Trejo-Caballero,
Lucía Díaz-Patiño,
Marlen González-Reynac
et al.

Abstract: Rechargeable Zn-air batteries (ZABs) are safe energy storage systems, making them attractive for different applications, while their attractiveness can be boosted by adding natural constituents for eco-friendly disposability. In this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…This shows that the hydrogel sensor not only has unique sensing performance but also high sensitivity over a wide range of strain. 6,50,51 To evaluate the stability and repeatability of the PVA-15/ SG-4/3 hydrogel strain sensing, the hydrogel strain sensor was tested for 200 consecutive stretch-unload cycles under 50% strain. As shown in Fig.…”
Section: Electrical Properties Of the Pva/sg Hydrogelmentioning
confidence: 99%
See 2 more Smart Citations
“…This shows that the hydrogel sensor not only has unique sensing performance but also high sensitivity over a wide range of strain. 6,50,51 To evaluate the stability and repeatability of the PVA-15/ SG-4/3 hydrogel strain sensing, the hydrogel strain sensor was tested for 200 consecutive stretch-unload cycles under 50% strain. As shown in Fig.…”
Section: Electrical Properties Of the Pva/sg Hydrogelmentioning
confidence: 99%
“…The absorbance of the solution at 570 nm was measured with an enzyme-labeled instrument. Cell viability was calculated using eqn (6) and taken from the average of three measurements. In eqn (6), OD 570 (sample) and OD 570 (control) are the absorbance values of the test and control groups, respectively.…”
Section: In Vitro Cell Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This polymer is hydrophilic, biodegradable, highly biocompatible, non-toxic, and non-immunogenic [ 158 , 159 , 160 , 161 , 162 , 168 , 169 , 170 ]. In addition to being sustainable, it is safe [ 171 ] and eco-friendly [ 133 , 172 , 173 ], and is well known for its low cost and wide natural abundance [ 130 , 160 , 161 , 162 , 167 , 173 ].…”
Section: Polymersmentioning
confidence: 99%
“…In 2022, Choi et al reported that itaconic acid (IA)‐based crosslinked poly(itaconic acid) (PIA) highly absorbent polymers (c‐PIAS) prepared by free radical polymerization with potassium peroxy sulfate as the raw material for the environmentally friendly, highly absorbent hydrogel gels were prepared by free radical polymerization with potassium persulfate 14 . In 2023, M. E. Trejo‐Caballero et al synthesized bio‐polymerized hydrogels (bio‐hydrogels) using a low eutectic solvent (DES), poly(itaconic acid) (PIA), and polysaccharides crosslinked with 2‐hydroxyethyl methacrylate (HEMA) 15 …”
Section: Introductionmentioning
confidence: 99%